3D bioprinting of dECM/Gel/QCS/nHAp hybrid scaffolds laden with mesenchymal stem cell-derived exosomes to improve angiogenesis and osteogenesis. (1st April 2023) - Kang, Yue; Xu, Jie; Meng, Ling'ao; Su, Ya; Fang, Huan; Liu, Jiaqi; Cheng, Yuen Yee; Jiang, Daqing; Nie, Yi; Song, Kedong
Abstract: Craniofacial bone regeneration is a coupled process of angiogenesis and osteogenesis, which, associated with infection, still remains a challenge in bone defects after trauma or tumor resection. 3D tissue engineering scaffolds with multifunctional-therapeutic properties can offer many advantages for the angiogenesis and osteogenesis of infected bone defects. Hence, in the present study, a microchannel networks-enriched 3D hybrid scaffold composed of decellularized extracellular matrix (dECM), gelatin (Gel), quaterinized chitosan (QCS) and nano-hydroxyapatite (nHAp) (dGQH) was fabricated by an extrusion 3D bioprinting technology. And enlightened by the characteristics of natural bone microstructure and the demands of vascularized bone regeneration, the exosomes (Exos) isolated from human adipose derived stem cells as angiogenic and osteogenic factors were then co-loaded into the desired dGQH20 hybrid scaffold based on an electrostatic interaction. The results of the hybrid scaffolds performance characterization showed that these hybrid scaffolds exhibited an interconnected pore structure and appropriate degradability (>61% after 8 weeks of treatment), and the dGQH20 hybrid scaffold displayed the highest porosity (83.93 ± 7.38%) and mechanical properties (tensile modulus: 62.68 ± 10.29 MPa, compressive modulus: 16.22 ± 3.61 MPa) among the dGQH hybrid scaffolds. Moreover, the dGQH20 hybrid scaffold presented good antibacterial activities (against 94.90 ± 2.44% of Escherichia coli and 95.41 ± 2.65% of Staphylococcus aureus, respectively) as well as excellent hemocompatibility and biocompatibility. Furthermore, the results of applying the Exos to the dGQH20 hybrid scaffold showed that the Exo promoted the cell attachment and proliferation on the scaffold, and also showed a significant increase in osteogenesis and vascularity regeneration in the dGQH@Exo scaffolds in vitro and in vivo . Overall, this novel dECM/Gel/QCS/nHAp hybrid scaffold laden with Exo has a considerable potential application in reservation of craniofacial bone defects.